EKSISTENSI TARI LIKURAI SUKU BELU DI DESA BHAKTI JAYA KECAMATAN MELIAU KABUPATEN SANGGAU - Nahak, Innocentia Marta Abuk; Istiandini, Winda; Tindarika, Regaria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
PROVINSI KALIMANTAN BARAT dan Nahak Marta Abuk, Innocentia. 2022. The purpose of conducting this research is describing the existence of Likurai dance. The study case is about the development and the starting point of the existence of Likurai traditional dance of Belu Tribe in Bhakti Jaya Village, district of Meliau, the regency of Sanggau, West Kalimantan Province. Descriptive methodology in a form of qualitative research and using an anthropology approach. The sources of data were collected using observation, interview, and documentation, with key sources namely, Mr. Dominikus Nahak, Mr. Muhammad Iwanie and Miss Ursula Uluk. Techniques to test validity using extension of observation and Triangulating of compiled data sources was systematically analyzed. Likurai dance is a traditional dance that was originally came from a village called Kereana, Botin Leobele district, the regency of Malaka, East Nusa Tenggara. The dance was introduced by a transmigrant society that was migrated from East Nusa Tenggara to Bhakti Jaya Village, the district of Meliau, Sanggau regency, West Kalimantan in the year of 1992. The dance started to develop and became well-known since 1998 until 2019. The uniformity of the transmigrant society is one of the main reasons behind the sustainability of Likurai dance in Bhakti Jaya Village. On the other, there is a risk that this traditional dance would be fading away due to the lack of the dance personnel and lack of interest in the younger generation as well as lack of assistance and motivation from the local government is feared to be an obstacle to the development of Likurai Dance.